NEW THERAPEUTIC AGENTS IN NEUROSARCOIDOSIS TREATMENT - Maric, Nikola; Golubovic, Aleksa; Belic, Slobodan; Djurdjevic, Natasa; Milivojevic, Ivan; Geratovic, Milos; Stjepanovic, Mihailo (Srpski medicinski časopis Lekarske komore, 2022)
Neurosarcoidosis is a relatively common extrapulmonary form of sarcoidosis. It is characterized by variable clinical presentation, low probability of spontaneous remission, and significant impact on the quality of life, as well as potential increase in mortality. In addition to corticosteroids, other drugs are used in the treatment of neurosarcoidosis, such as methotrexate, azathioprine, mycophenolate mofetil, tumor necrosis factor α (TNF-α) inhibitors, infliximab and adalimumab. In this paper, by reviewing the available literature, we have attempted to consolidate the current knowledge and novelties in the treatment of neurosarcoidosis, for the purpose of assisting physicians in their day-to-day clinical work. Previous studies still favor pulsed doses of corticosteroids, while other forms of therapy have proven beneficial only in individual cases. However, it should be noted that additional research is needed in order to successfully develop individual therapy.